Comparative evaluation of performance and emissions of CNG engine for heavy-duty vehicles fueled with various caloric natural gases. (1st May 2019) - Park, Cheolwoong; Kim, Changgi; Lee, Sangho; Lee, Sunyoup; Lee, Janghee
Abstract: In the present study, an 11 l inline six-cylinder natural gas engine of the stoichiometric combustion type, which is implemented in city buses, is used in wide-open throttle and transient mode cycle tests. This is done to assess the effects of natural gas fuel composition on the full-load performance and emissions characteristics under a mode test for emission standards. Experiments were carried out on three types of compositions: The minimum calorific value of new natural gas supply regulations, the average composition of new supply regulations applied, and liquid natural gas weathered over three weeks. The torque of the engine increases proportionally with the calorific value. When the fuel supply is controlled in inverse proportion to the calorific value of a fuel, the torque of gas with a lower calorific value than the reference fuel is decreased. When gas with a lower calorific value than the reference fuel is used, the amount of carbon monoxide increases slightly, and nitrogen oxide emission increases significantly. However, after calibration of the fuel amount by adaptive learning, in experiments under a world harmonized transient cycle mode test condition, the nitrogen oxides are reduced again below the emission limit and meet the regulation. Highlights: The torque of the engine increases as the calorific value is proportional. The thermal efficiency decreases as the calorific value of the fuel decreases. CO2 emissions increase as the calorific value of the fuel increases. Low calorific value gas meets the EURO-VI emission gas standards regardless of AL. High calorific value gas does not satisfy the EURO-VI emission gas standards with AL.